Development of trigonometry course module based on problem solving - Wicaksono, Arief Budi; Chasanah, Aprilia Nurul; Gunawan, Gunawan (Universitas Mercu Buana Yogyakarta, 2024)
Problem-solving is one of the most important skills for students to have. One of the efforts to develop students' problem-solving skills is to conduct learning using modules designed to improve problem-solving abilities. The purpose of this research is to develop a good quality trigonometry course module that meets the criteria of being valid, practical, and effective. The type of research conducted is research on the development of the Borg & Gall model. The Borg & Gall model consists of potential and problem phases, data collection, product design, design validation, usage trials, product revisions, product trials, design revisions, product revisions, and mass production. The subjects of this study were the first semester students of the Mathematics Education Study Program, Tidar University. Data were analyzed based on the level of validity, practicality, and effectiveness of the module. The results showed that the module was included in the valid category and the practical category. The aspect of effectiveness based on the results of the posttest with problem-solving questions is said to be effective. The result of the development in this research is the product of a trigonometry course module based on problem solving that is valid, practical, and effectively used for mathematics education students. The contribution of this research is that the module can be used in trigonometry lectures.